Analysis of Environmental Accounting as a Form of Corporate Social Responsibility in Environmental Management Effort to Reduce Externalities Impact (Case Study In Rumah Sakit Islam Malang-UNISMA) - Nur, Aji Kusuma M.; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The company is never separated from the environment. Their interaction often leads to serious problems. Negative impacts are called externalities. The magnitudes of the impact of externalities encourage the desire to exercise control over the activities undertaken by the company. Environmental accounting is defined as the prevention, reduction, or avoidance and impact on the environment. This research is a descriptive qualitative study using case studies method on Rumah Sakit Islam Malang-UNISMA. This study aims to determine how to conduct environmental management, the application of the concept of environmental accounting, and the form of the financial statements of the environment in the annual reports of Rumah Sakit Islam Malang-UNISMA. Problem analysis is done through the following steps: (1) observe and analyze a variety of environmental management activities (2) collect, identify, and analyze the environmental costs arising from the activities of environmental management (3) collect and analyze information regarding the reporting of environmental costs in the report annual financial. The survey results revealed that Rumah Sakit Islam Malang has not been seriously implemented the concept of environmental accounting. This can be seen in the identification of costs, there is no aspect of measurement and classification clear how a costs is categorized as environmental costs or not. This led that some environmental costs are not budgeted for in the annual budget of the hospital. The results also showed that the Rumah Sakit Islam Malang had not made the environmental financial report. Keywords: Environmental Accounting, The Effort of Environmental Management